2007
DOI: 10.1111/j.1365-2036.2007.03555.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non‐adherence to medication in inflammatory bowel disease patients

Abstract: SUMMARY BackgroundInflammatory bowel diseases are chronic conditions requiring medication throughout life to treat the disease and control the risk of relapse and colorectal cancer. Adherence to prescribed drugs is therefore crucial to their management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
92
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 38 publications
14
92
3
2
Order By: Relevance
“…Similarly, in the study of Shale and Riley [21] , in addition to being young, having education beyond the age of 16 years and being in full-time employment, being prescribed a 3-times-a-day regimen was identified as predictor for non-adherence. The need to take medicine during working hours (P = 0.001, OR: 3.5, 95% CI: 2.27-5.26), and multiple daily doses (P = 0.045, OR: 2.8, 95% CI: 0.99-7.70) were significantly associated with non-adherence in adults [22] , which was also confirmed by other studies [20,21] . Similarly, adolescents whose regimen involved more than one daily medication administration had more adherence barriers [26] .…”
Section: Drug Type and Dosing Regimessupporting
confidence: 78%
See 4 more Smart Citations
“…Similarly, in the study of Shale and Riley [21] , in addition to being young, having education beyond the age of 16 years and being in full-time employment, being prescribed a 3-times-a-day regimen was identified as predictor for non-adherence. The need to take medicine during working hours (P = 0.001, OR: 3.5, 95% CI: 2.27-5.26), and multiple daily doses (P = 0.045, OR: 2.8, 95% CI: 0.99-7.70) were significantly associated with non-adherence in adults [22] , which was also confirmed by other studies [20,21] . Similarly, adolescents whose regimen involved more than one daily medication administration had more adherence barriers [26] .…”
Section: Drug Type and Dosing Regimessupporting
confidence: 78%
“…In contrast, other studies reported low adherence rates after long-term remission [3,22] . Very high non-adherence rates (74.3%) were reported for azathioprine in CD patients who were in long-term (> 48 mo) clinical remission [20] .…”
Section: Age and Disease Durationmentioning
confidence: 43%
See 3 more Smart Citations